On \(g\)-scattered spaces - Xiaomin Li (Scientia Series A: Mathematical Sciences, 2025)
This paper is devoted to investigate scatteredness on generalized topological spaces. The concept of  \(g\)-scattered spaces is introduced. Their characterizations, properties and mapping theorems are obtained.
Keywords: GTS’s; g-scattered spaces; g-dense sets; g-isolated points; g-limit points; g-derived sets; GT-sums